ZBrush character creation advanced digital sculpting - Spencer, Scott 1975- (Indianapolis Wiley, 2011)
"A stunning, content-rich update to this top-selling ZBrush guide! This second edition of ZBrush Character Creation has been fully updated for ZBrush 4, the newest version of this fascinating and popular 3D sculpting software. ZBrush enables users to create detailed organic models using a brush-based toolset and tablet. The startling results look as though they've been painted with real brushes and oils, and ZBrush is increasingly popular for use in film, game, and broadcast pipelines. Author Scott Spencer is embedded in the ZBrush community and his movie credits include Harry Potter and The Order of the Phoenix and the upcoming The Hobbit. Learn Spencer's invaluable techniques for texturing, chiseling, posing, costuming, and more with his newest ZBrush guide. Explains ZBrush 4, the newest version of the revolutionary software tool for creating 3D organic models in a way that appears to be traditionally painted or sculpted Shows you how get the most out of ZBrush, from the fundamentals to new tools for texturing, chiseling, and costuming Offers plenty of insights and professional techniques for creating characters for films and games, drawing from the author's own experience on such films as Harry Potter and The Order of the Phoenix and The Hobbit Demonstrates the author's own techniques of using traditional sculpting and painting concepts and applying them to digital art for greater artistry Discover the beauty of ZBrush with this colorful, in-depth guide."-- Provided by publisher.
Keywords: ZBrush; Computer graphics; COMPUTERS / Image Processing